The Sérgio Buarque de Holandas Weberian thought as an Explanation for Corruption in Brazilian Society (Global Journal of Human-Social Science, 2020)
The present article aims to expose more precisely the influences of Max Weber's thinking on Sérgio Buarque de Holanda's main work: Raízes do Brasil. Considering that the work of Holanda represents a fundamental contribution to the sociological studies on corruption in Brazil, it is necessary, in order to reduce recurring misunderstandings, a detailed presentation of the Weberian theoretical basis and its incorporation along Raízes do Brasil. Holanda's perspective on the constitutive elements of Brazilian culture and institutions is in constant dialogue with Weberian notions of "traditional domination," "affective social action," "patrimonialism," and "traditional social action". Such conceptions are circumscribed in the great theory of social rationalization produced by the german sociologist and, in the work of the Brazilian historian, result in the diagnosis of a society deeply oriented by personalism, traditionalism, patrimonialism and cordiality. Finally, we tried to demonstrate how these characteristics of Brazilian society still benefit the practice of corruption insofar as they do not produce the formally rationalized culture, guided by the valorisation of the legal norms compliance, and do not create rigid and impersonal institutions to limit the relations between the public sphere and the private sphere.
Keywords: corruption; roots of brazil; sérgio buarque de holanda; weberian sociology; brazilian social studies